Resveratrol contributes to NK cell-mediated breast cancer cytotoxicity by upregulating ULBP2 through miR-17-5p downmodulation and activation of MINK1/JNK/c-Jun signaling - Bisha Ding; Jie Li; Jia-Lin Yan; Chun-Yan Jiang; Ling-Bo Qian; Jie Pan (Frontiers in Immunology)
BackgroundsNatural killer (NK) cell mediated cytotoxicity is a crucial form of anti-cancer immune response. Natural killer group 2 member D (NKG2D) is a prominent activating receptor of NK cell. UL16-binding protein 2 (ULBP2), always expressed or elevated on cancer cells, functions as a key NKG2D ligand. ULBP2-NKG2D ligation initiates NK cell activation and subsequent targeted elimination of cancer cells. Enhanced expression of ULBP2 on cancer cells leads to more efficient elimination of these cells by NK cells. Resveratrol (RES) is known for its multiple health benefits, while current understanding of its role in regulating cancer immunogenicity remains limited. This study aims to investigate how RES affects the expression of ULBP2 and the sensitivity of breast cancer (BC) cells to NK cell cytotoxicity, along with the underlying mechanisms.MethodsThe effects of RES on ULBP2 expression were detected with qRT-PCR, western blot, flow cytometry analysis and immunohistochemistry. The effects of RES on sensitivity of BC cells to NK cell cytotoxicity were evaluated in vitro and in vivo. The target gene of miR-17-5p were predicted with different algorithms from five databases and further confirmed with dual-luciferase reporter assay. Overexpression and knockdown experiments of miR-17-5p and MINK1 were conducted to investigate their roles in regulating ULBP2 expression and subsequent JNK/c-Jun activation. The JNK inhibitor sp600125 was utilized to elucidate the specific role of JNK in modulating ULBP2 expression.ResultsRES increased ULBP2 expression on BC cells, thereby augmenting their vulnerability to NK cell-mediated cytotoxicity both in vitro and in vivo. RES administration led to a reduction in cellular miR-17-5p level. MiR-17-5p negatively regulated ULBP2 expression. Specifically, miR-17-5p directly targeted MINK1, leading to its suppression. MINK1 played a role in facilitating the activation of JNK and its downstream effector, c-Jun. Furthermore, treatment with sp600125, a JNK inhibitor, resulted in the suppression of ULBP2 expression.Conclusions：RES potentiates ULBP2-mediated immune eradication of BC cells by NK cells through the downregulation of miR-17-5p and concurrent activation of the MINK1/JNK/c-Jun cascade. This finding identifies RES as a potentially effective therapeutic agent for inhibiting BC progression and optimizing NK cell-based cancer immunotherapy.